2021
DOI: 10.3390/jzbg2020017
|View full text |Cite
|
Sign up to set email alerts
|

Education Is Entertainment? Zoo Science Communication on YouTube

Abstract: YouTube is the dominant online video-sharing platform and offers zoos an opportunity to engage a vast audience with conservation content. As there is limited research evaluating how zoos currently utilize YouTube, we cataloged and evaluated the content of 20 zoological organizations (focusing on the top 1000 most viewed videos from each channel) from 2006 to 2019. Separately, educational content in a subsample of the most viewed and recently produced videos from three zoo-YouTube channels was catalogued and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…It should be noted that as McClain [2019] focused only on marine taxa, this comparison is limited. Other studies have found stronger audience preference for mammals [Hausmann et al, 2018;Kidd et al, 2018;Llewellyn and Rose, 2021;Rose, Hunt and Riley, 2018]. However, these studies also found that several non-taxonomic variables can influence audience engagement, including the use of colourful or novel material, content that evokes awe, or positive or emotive reactions [McClain, 2019] or the promotion of interesting behavioural or physical traits [Kidd et al, 2018].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It should be noted that as McClain [2019] focused only on marine taxa, this comparison is limited. Other studies have found stronger audience preference for mammals [Hausmann et al, 2018;Kidd et al, 2018;Llewellyn and Rose, 2021;Rose, Hunt and Riley, 2018]. However, these studies also found that several non-taxonomic variables can influence audience engagement, including the use of colourful or novel material, content that evokes awe, or positive or emotive reactions [McClain, 2019] or the promotion of interesting behavioural or physical traits [Kidd et al, 2018].…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have found text to influence public engagement with Instagram posts [Jarreau, Dahmen and Jones, 2019], suggesting that both image and textual content should be taken into account when examining audience engagement on Instagram. Audience sentiment and engagement with online content can also be influenced by variables such as how close or far away the subject is [Jarreau, Dahmen and Jones, 2019], the tone (humorous or serious) of the post [Lenda et al, 2020], novelty [Kidd et al, 2018;McClain, 2019] and entertainment value [Lessard, Whiffin and Wild, 2017], length [Llewellyn and Rose, 2021], whether it contains breaking news [Jarreau, Dahmen and Jones, 2019;Lessard, Whiffin and Wild, 2017], as well as significant events like the rediscovery of species thought to be extinct [Lennox et al, 2020]. In their search for the most 'Instagrammable' bird, Thömmes and Hayn-Leichsenring [2021, p. 2] found that blue colours as well as "interestingness, idiosyncrasy, and the situational context all play their part in the aesthetic appeal of bird photos to the human observer".…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, overall, we believe that a greater effort should be undertaken by each zoo to enhance dissemination and public engagement about lemur conservation projects. In any case, more zoos certainly mean more communication initiatives [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social media is a powerful tool for the wider dissemination of information that emphasizes the importance of engagement with biodiversity conservation and welfare in the zoo ( Light and Cerrone, 2018 ; Rose et al, 2018 ; Llewellyn and Rose, 2021 ). Targeted and thoughtful use of social media can promote wider conservation objectives to audiences that may otherwise be hard to reach, and promote access to biodiversity/conservation education information in a more accessible manner ( Bezanson et al, 2022 ).…”
Section: Promoting Connectivity With Naturementioning
confidence: 99%